Konfigurasi Dasar MikroTik dan Implementasi Jaringan pada Kegiatan Operasional IT di PT Pembangunan Jaya Ancol - Hiya Iklima Usman; Ahmad Fikri Salim; Muhammad Fikri (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
This internship (Kerja Praktik) was conducted at PT Pembangunan Jaya Ancol in the IT and Project Management Office Division with the objective of providing practical work experience for students in the field of computer networking and information technology. The main focus of this internship was the basic configuration of MikroTik devices and their implementation in supporting the company’s IT operational activities. The methods applied during the internship included workplace observation, hands-on practice in network device configuration, and documentation of IT operational activities. The basic configurations performed consisted of network topology design, IP address configuration on ether and bridge-hotspot interfaces, as well as network connectivity testing to ensure proper system operation. In addition, the student was involved in supporting IT operational tasks, such as preparing computer equipment and network systems at the Ancol ticketing area ahead of the New Year celebration. The results of this internship indicate that basic MikroTik configuration plays a crucial role in maintaining network stability and ensuring smooth IT operations within the company. Through this internship, the student gained technical knowledge and practical experience that are highly relevant as preparation for entering the professional world in the field of information technology.